Study on Au coating of ceramic-lined thin-wall vacuum chamber for HIAF. (February 2021) - Li, C.C.; Luo, C.; Liu, J.L.; Yang, J.C.; Shen, G.D.; Meng, J.; Yang, W.S.; Yang, Y.Q.; Wu, J.X.; Zhu, G.Y.; Xia, J.W.; Xie, W.J.; et al.
Abstract: HIAF-BRing, the main synchrotron accelerator of the High Intensity Heavy-Ion Accelerator Facility, requires an average pressure lower than 1 × 10 −9 Pa and the magnetic field increase rate no less than 12 T/s to fulfill radioactive beam physics and high energy density physics experiments. To reduce the eddy current effect and the gap size of dipoles compared to the thin-wall stainless steel vacuum chamber with reinforced ribs, a new design of ceramic-lined vacuum chamber with wall thickness 0.3 mm has been proposed by IMP. In order to effectively reduce the beam impedance and the desorption rate of ceramic materials, Au coating on ceramic (Yttria stabilized zirconia) by magnetron sputtering has been carried out. The adhesive force of Au film is 28.1 MPa measured by scratch test while the crystalline size of Au particle is in the range of 15.7–21.4 nm by X-ray diffraction (XRD). The longitudinal impedances of four types of round-ring-lined 0.6-m-long straight stainless-steel tubes and the ultimate pressure of the new designed vacuum chamber (uncoated vs Au-coated) have been measured to verify the feasibility of this method. Highlights: A new design of ceramic-lined vacuum chamber with wall thickness 0.3 mm has been proposed to reduce the eddy current effect and the gap size of dipoles, where the ceramic rings are Au-coated and a prototype has been designed and manufactured to test the concept. The ceramic ring is made by yttrium stabilized zirconia, which has very good mechanical strength and toughness. Compared to the thin-walled stainless steel vacuum chamber with reinforced ribs, the gap size of the dipole decreases significantly and therefore the magnets manufacturing and operating cost reduce accordingly. In order to reduce the beam impedance and the desorption rate of the ceramic surface, the ceramic rings have been coated with a 1 μm Au film. The Au coating has been characterized by several surface analysis technologies. Film quality proved to be good and adhesion was tested to be 28.1 MPa.